(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Ischemic stroke remains one of the leading causes of death and long-term disability worldwide, characterized by the sudden loss of blood flow to brain tissue, resulting in neuronal injury. The acute management of ischemic stroke has evolved with the introduction of neuroprotective agents such as Xavron (Edaravone), a potent free radical scavenger that minimizes oxidative stress and neuronal apoptosis. This paper examines the effectiveness of Xavron in the treatment of ischemic stroke during the acute period. Through analysis of recent clinical trials, neurophysiological studies, and biochemical data, this article explores its pharmacological mechanisms, therapeutic benefits, and limitations. The findings indicate that Xavron significantly improves neurological outcomes, reduces infarct volume, and enhances recovery when administered early after stroke onset. Its integration into acute ischemic stroke protocols offers promising prospects for neuroprotection and improved quality of life among stroke patients.